Designing a BDI agent model for behavioural change process - Adegoke, Ojeniyi; Yusof, Yuhanis; Ab. Aziz, Azizi (2014)
Belief-Desire-Intention (BDI) model is well suited for describing agent’s mental state.The BDI of an agent represents its motivational stance and are the main determinant of agent’s actions. Therefore, explicit understanding of the representation and modelling of such motivational stance plays a central role in designing BDI agent with successful behavioural change interventions.Nevertheless, existing BDI agent models do not represent agent’s behavioural factors explicitly.This leads to a gap between design and implementation where psychological reactance has being identified as the cause of BDI agent behavioural change interventions failure. Hence, this paper presents a generic representation of BDI agent model based on behavioural change and psychological theories.The objective of this proposed BDI agent model is to bridge the gap between agent design and implementation for successful agent-based interventions.The model will be realized in an agent-based application that motivates children towards oral hygiene.